Analysis of Physics Problem Solving Skills of Junior High School Students through PBL-HOTS on Magnetism Material - Nurhasan Ropi'i; Sunyoto Eko Nugroho; Ellianawati Ellianawati (Universitas Negeri Semarang, 2025)
Critical thinking and problem-solving skills are essential components of 21st-century education goals. Weak problem-solving and higher-order thinking skills (HOTS) can become problematic for students studying physics, particularly in the context of magnetism. To address this issue, efforts are being made to improve physics problem-solving skills through the application of problem-based learning (PBL) and HOTS. The study aims to determine whether students' physics problem-solving skills are better when using PBL-HOTS compared to PBL alone. Additionally, the study aims to determine the improvement and profile of physics problem-solving skills according to Heller after the application of PBL-HOTS on magnetism material. The study employed a mixed-methods sequential explanatory pre-test post-test control group design. The participants were ninth-grade students from SMP Negeri 1 Kersana during the 2021/2022 academic year. The sample was selected using purposive sampling, with Class IX A as the experimental group and Class IX C as the control group. Data was collected using a physics problem-solving test, including descriptions, interviews, and post-test documentation checks. The t-test results indicate that students who applied PBL-HOTS had better physics problem-solving skills than those who applied PBL. Additionally, the N-Gain test showed a moderate increase in students' physics problem-solving skills after the application of PBL-HOTS, with an average N-Gain score of 0.4785. The results of interviews and examination of posttest documentation support Heller's profile of students' physics problem-solving skills. This includes indicators of focusing on the problem (84.69%), describing physics concepts (70.94%), planning solutions (87.81%), implementing problem-solving plans (95.63%), and evaluating solutions (46.88%).